THE CORRELATION BETWEEN MEMORY AND USES OF WORDS MEANINGS AND USAGES OF SEVENTH GRADE STUDENTS AT SMP N 5 SINGARAJA - Swadnyani, Ni Kadek; Tantra, Dewa Komang; Adnyani, Luh Diah Surya (Universitas Pendidikan Ganesha, 2018)
The objective of this research was to know whether there is any correlation between memory and uses of the words meanings and usages. There are there research problems were examined. It is about the total words meanings and usages remembered by the students, the uses of the words meanings and usages in the four language skills, and the correlation between memory and uses of the words meanings and usages. This research conducted at SMP N 5 Singaraja and the sample used was students in the seven grade consisted of 62 students. The data were collected using test and questionnaire. The result of test shows that the highest total number of words meanings and usages remembered by the students is 115 words (90%) from the total number of words is 128 words while the lowest total number of words meanings and usages remembered by the students is 64 words (50%). The most word class remembered by students in terms of word meanings and usages is noun that is 75% and word class adverb is 42% remembered by the students. The result of questionnaire shows that students used words meanings and usages frequently in reading. In reading, 62 students (100%) used words meanings and usages in terms of word class noun, verb, adjective, and adverb. The result of data analysis shows that there is a significant correlation between memory and uses of words meanings and usages. It could be seen by looking at the result of Point-Biserial Correlation coefficient r that is 0.564. Key Words: memory, uses of words meanings and usages